Fresh evidence in Canadian criminal law: 1910--2010 - Pollard, Dorette (University of Ottawa (Canada), 2010)
In the last four decades, there has been a dramatic increase in the number of fresh evidence cases before Canadian criminal law appellate courts. Yet when it was first introduced at the turn of the last century, this rule of evidence was meant to be an exception to the principle of the finality of judgments, to be used only on those rare occasions when a miscarriage of justice had occurred. It was intended to prevent the innocent from going to jailor worse, from perishing on the gallows. Historically, fresh evidence was used but rarely prior to 1970. However, starting in the mid 1970s these applications have grown significantly, exploding after the early 1980s. Based on an analysis of an initial database of 2116 fresh evidence matters, the thesis examines the possible reasons for this phenomenon and concludes that there is a direct correlation between the rise in the number of fresh evidence cases after 1970 and the advances in science, including the use of new evidence, such as DNA and expert forensic evidence in criminal law cases. But if the advances in science have made a significant contribution to the growth of fresh evidence applications, it was the advent of the Canadian Charter of Rights and Freedoms that brought a sea change to Canadian criminal law fresh evidence jurisprudence. Through a theoretical framework constructed around the search for truth, rights and theories of fairness, the thesis traces the evolution of appellate adjudication in this area of law that from its origins was meant to be used but rarely in the interests of the administration of justice to prevent miscarriages of justice.
Keywords: History, Canadian.; Law.